แบบจำลองพื้นที่การใช้ประโยชน์ร่วมกันของกระทิงและช้างป่าในเขตรักษาพันธุ์สัตว์ป่าภูเขียว จังหวัดชัยภูมิ - ผลานิสงค์ คชกริช; ไตรสุรัตน์ ยงยุทธ; ภูมิภาคพันธ์ นริศ; ศุขเฉลิม ดวงใจ; โภฌชงค์ สุชาติ (Thai Journal of Science and Technology, 2019)
Abstract This article attempted to predict the distributions and co-habitats of gaur (Bos gaurus) and elephant (Elephas maximus) at Phu Khieo Wildlife Sanctuary (PKWS), Chaiyaphum Province. The research study of the wildlife distribution was evaluated by using maximum entropy (MaxEnt) model. The selected mammal species included gaur and elephant, and their occurrences were gathered from smart patrols conducted by the rangers during 2012-2016. The results revealed that at the considerable environment factors on the wildlife distribution included distance from saltlicks (41.50 %), land use (13.50 %), precipitation of wettest month (8.10 %), distance from rangeland (4.95 %), distance from villages (6.85 %), slope (5.40 %) and distance from water sources (4.3 %). Additionally, the maximum range sizes of the sanctuary’s area were predicted to cover 486.21 and 399.57 sqkm., for gaur and elephant, respectively. Furthermore, the co-habitats or overlapped habitats for 2 species cover 315.92 sqkm, most areas in the northern part. All habitats suitable for the wildlife distribution are 569.86 sqkm. Keywords: wildlife; distribution; Phu Khieo Wildlife Sanctuary